Opioid Use Among Veterans of Recent Wars Receiving Veterans Affairs Chiropractic Care. (7th September 2018) - Lisi, Anthony J; Corcoran, Kelsey L; DeRycke, Eric C; Bastian, Lori A; Becker, William C; Edmond, Sara N; Goertz, Christine M; Goulet, Joseph L; Haskell, Sally G; Higgins, Diana M; Kawecki, Todd; Kerns, Robert D; et al.
Abstract: Objective: To examine patient sociodemographic and clinical characteristics associated with opioid use among Veterans of Operations Enduring Freedom/Iraqi Freedom/New Dawn (OEF/OIF/OND) who receive chiropractic care, and to explore the relationship between timing of a chiropractic visit and receipt of an opioid prescription. Methods: Cross-sectional analysis of administrative data on OEF/OIF/OND veterans who had at least one visit to a Veterans Affairs (VA) chiropractic clinic between 2004 and 2014. Opioid receipt was defined as at least one prescription within a window of 90 days before to 90 days after the index chiropractic clinic visit. Results: We identified 14, 025 OEF/OIF/OND veterans with at least one chiropractic visit, and 4, 396 (31.3%) of them also received one or more opioid prescriptions. Moderate/severe pain (odds ratio [OR] = 1.87, 95% confidence interval [CI] = 1.72–2.03), PTSD (OR = 1.55, 95% CI = 1.41–1.69), depression (OR = 1.40, 95% CI = 1.29–1.53), and current smoking (OR = 1.39, 95% CI = 1.26–1.52) were associated with a higher likelihood of receiving an opioid prescription. The percentage of veterans receiving opioid prescriptions was lower in each of the three 30-day time frames assessed after the index chiropractic visit than before. Conclusions: Nearly one-third of OEF/OIF/OND veterans receiving VA chiropractic services also received an opioid prescription, yet the frequency of opioid prescriptions was lower after the index chiropractic visit than before. Further study is warranted to assess the relationship between opioid use and chiropractic care.